Fibroadenoma of ectopic breast tissue in axilla: a case report - Korumilli, Ramesh Kumar; Srikanth, Jakkula; Muvva, Sri Harsha; Saka, Laxman (International Surgery Journal, 2018)
Fibroadenoma of ectopic breast tissue is a rare disease. It is very important to rule out malignancy as carcinoma commonly occurs in ectopic breast tissue. Here we report a case of 48 years old female presenting with complaints of swelling in right axilla since 3 months. Fine needle aspiration cytology suggested fibroadenoma of right breast. Ultrasonography of axilla revealed no other swellings apart from the fibroadenoma. Patient underwent excision and biopsy. Histopathology confirmed it as fibroadenoma of the ectopic breast tissue.